2022
DOI: 10.5114/ada.2022.120879
|View full text |Cite
|
Sign up to set email alerts
|

Demodicosis among immunocompromised patients: a review

Abstract: Introduction: Demodex mites (DM) are the most common ectoparasites of humans. Demodex folliculorum and Demodex brevis are the two species we are hosts for. Through the years there have been more data proving DM to be a pathogenic parasite. To this date it has not clear which groups of patients are clearly prone to develop demodicosis. Aim: To present a literature review in order to analyse and establish whether immunosuppressed patients are prone to develop demodicosis. Material and methods: Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The precise etiology of demodicosis is unclear, but local and systemic immune status likely plays a role. Demodex ‐associated dermatoses have been reported in settings that include human immunodeficiency virus infection, solid organ transplantation, hematological malignancy, chemotherapy such as 6‐mercaptopurine and vincristine, and use of topical steroids 3,5,6 . In addition, studies have demonstrated that the density of Demodex mites on the skin is greater in patients undergoing treatment with immunosuppressive medications 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise etiology of demodicosis is unclear, but local and systemic immune status likely plays a role. Demodex ‐associated dermatoses have been reported in settings that include human immunodeficiency virus infection, solid organ transplantation, hematological malignancy, chemotherapy such as 6‐mercaptopurine and vincristine, and use of topical steroids 3,5,6 . In addition, studies have demonstrated that the density of Demodex mites on the skin is greater in patients undergoing treatment with immunosuppressive medications 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Demodex-associated dermatoses have been reported in settings that include human immunodeficiency virus infection, solid organ transplantation, hematological malignancy, chemotherapy such as 6-mercaptopurine and vincristine, and use of topical steroids. 3,5,6 In addition, studies have demonstrated that the density of Demodex mites on the skin is greater in patients undergoing treatment with immunosuppressive medications. 7 The clinical morphology of demodicosis may include erythema, rosacea-like lesions and folliculitis, 8 and may mimic cutaneous lupus erythematosus or dermatomyositis, leading to further immunosuppressive treatment and in turn worsening of the eruption, as in our patient.…”
Section: F I G U R E 2 Demodex Mites In a Follicular Orifice (Hematox...mentioning
confidence: 99%